Impact of Diaphragm Behavior on the Seismic Design of Low-Rise Steel Buildings - Rogers, Colin A.; Tremblay, Robert (Engineering Journal, 2010)
Modern building codes allow engineers to use reduced seismic loads in design provided that the seismic load resisting system (SLRS) of the structure is adequately designed and detailed to withstand strong ground shaking through ductile inelastic response. This approach has been adopted by the North American model codes which typically include special provisions to achieve satisfactory inelastic seismic performance. Single-story buildings often incorporate a steel roof deck diaphragm that is relied on to transfer lateral loads to the vertical bracing bents. The vertical braces are usually selected as the energy dissipating fuse element, while the diaphragm and other elements in the SLRS should be designed such that their capacity exceeds the nominal resistance of the braces. Steel bracing members designed for compression inherently possess significant reserve strength when loaded in tension, which means that large brace tension loads must be considered in the design of the surrounding protected structural components. Capacity design seismic provisions have led to the need for much thicker roof deck panels and more closely spaced diaphragm connection patterns compared with past practice in Canada. This paper describes the current U.S. seismic design approach and provides examples as it is applied to single-story buildings and their diaphragms. An overview of the related aspects of an on-going research project on the flexibility and ductility of the roof diaphragm in low-rise steel buildings is also included.